Mechanical properties of ultra-fine grain aluminium AL6063 and pure copper processed by equal channel angular extrusion method - Nemati, Jamshid (2015)
Severe plastic deformation (SPD) is one of the processes used to refine the microstructure of materials among which the Equal Channel Angular Extrusion (ECAE) is the most common method. ECAE has gained much interest over the past decades. In this study, pure copper and aluminum alloy 6063 grain refinement were performed using the ECAE method. The materials were extruded up to eight and six passes at room and 200°C temperatures with a constant ram speed of 20 and 30 mm/min, respectively, following route A through a die angle of 90° between the die channels. Optical microscopic examinations revealed pure copper grain refinements in the range of 32 μm to 4 μm after eight passes whereas for Al-6063 alloy the grain diameter reduced from 45 μm to 2.8 μm after six passes of ECAE. The extruded specimens were tested under quasi-static, medium and high strain rate loadings using various testing machines. Mechanical properties of the extruded material were obtained at different strain rates. For the pure copper, it was found that the maximum increased of ultimate strength of 80% occurred after the second pass for the V=200 mm/min. The total increase of ultimate strength after eight passes was around 100%. Furthermore,hardness, increased to a maximum of 36% after eight passes. The results of Al-6063 tensile tests indicated that the tensile yield stress (YS) and ultimate tensile strength (UTS) of the extruded specimens increased significantly after 5 passes of ECAE process. The average increase was found to be around 70%,regardless of the tension velocities. The hardness measurements were made on different locations of the billet. For Al-6063, the results indicated around 90% increase in microhardness after 5 passes. The results for pure copper illustrated that the most increase of hardness (about 18%) occurs after the 2nd pass. A total of around 36% increase in hardness was observed after 8 passes. A maximum increase in impact energy absorption of 100% was achieved from Charpy tests after eight passes and 90% after six passes of the ECAE process for pure copper and Al-6063 alloy, respectively. In addition, bending fatigue test results indicates that for fatigue tested pure copper specimens, the results of fatigue tests indicated that a significant improvement in fatigue life occurred after the 2nd pass. For low stresses, a maximum increase in fatigue resistance of approximately 500% was observed. The results of fatigue tested Al-6063 specimens indicate that major improvements in fatigue resistance occurred after the first pass. The impact strength of extruded specimens was also evaluated for different passes at a strain rate of 1800 s-1 using Split-Hopkinson pressure bar (SPHB). The results indicated that the major strength improvement for Al-6063 and pure copper in the 5th and 6th passes and 6th and 8thoccurred, respectively. Finally, ECAE process was simulated using the DEFORM- 3D software through a three-dimensional analysis.